SIGN LANGUAGE IN BTS' MUSIC VIDEO "PERMISSION TO DANCE" BECOMES HAPPINESS FOR THE DEAF - Fathin Shalihah; Nina Yuliana (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
This research analyzes the use of Sign Language in the music video "Permission to Dance" by BTS and its impact on the deaf community. BTS integrated Korean Sign Language and International Sign Language into the choreography of this song, with the aim of saying goodbye to Covid-19 and bringing happiness after difficult times. This Sign Language choreography has a message of peace, happiness and unity for everyone, including those with special needs. This music video received appreciation from WHO because it allows people with hearing impairments to enjoy music. This research uses a constructivist paradigm, a qualitative approach with phenomenological and observational methods. Referring to the SOR communication theory from Houland, et al., where the communicator can provide a stimulus through his messages to the organism to change or adjust its behavior. Analysis of reactions from social media users shows that this music video is very liked and touching, especially by people with hearing loss. From the research results, it was concluded that the BTS music video "Permission To Dance" with Sign Language choreography had a positive impact on people with hearing impairments or hearing impairments.